Empowering elementary school students to become young nurses as movers and supervisors of healthy living behavior in SDIT Tahfizil Qur'an Islamic Centre Sumatera Utara - Siregar, Farida Linda Sari; Lufthiani; Asrizal (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Empowering students as elementary school students to become young nurses is an activity that can improve students' knowledge and skills so that they can become movers and supervisors for healthy behavior in the school environment. The method used in this service is the training of young nurses, mentoring, and evaluation. The material presented in the training of young nurses is how to care for wounds, personal hygiene care, how to wash hands with soap properly, how to measure weight and height, how to maintain cleanliness of the school environment, how to recognize signs and symptoms of diarrheal disease, and intestinal worms. It is hoped that through this training students can become movers and supervisors for healthy living behaviors in schools. Young nurses who are trained are expected to be able to do wound care, measure height, measure weight, teach how to wash hands with soap and conduct health education to other students. The results of this community service activity showed that most students had good knowledge, good attitude and good skills after attending training on washing hands with soap. Students' skills on how to treat wounds showed mostly good after attending training on how to treat wounds. Students' skills on how to measure height and weight showed a good overall after attending training on how to measure height and weight.